The effect of ammonia nitrogen, nitrite and pH on artificial incubation of red claw crayfish Cherax quadricarinatus eggs and growth of juveniles. (4th May 2022) - Yong‐chun, Wei; Shun, Cheng; Dan‐li, Wang; Mei‐li, Chi; Jian‐bo, Zheng; Yong‐yi, Jia; Fei, Li; Shi‐li, Liu; Yi‐nuo, Liu; Zhi‐min, Gu
Abstract: Artificial incubation is an effective way to increase the supply of red claw crayfish seed. In order to explore the effects of nitrite, ammonia nitrogen and pH on the eggs and nitrite on juvenile during in artificial incubation, four experiments were carried out. The results of Experiment I showed: (1) the hatching rate was less affected by nitrite, while the survival rate was greatly affected by nitrite. There were significant differences among the groups. (2) The analysis of the cubic regression equation showed a downward trend with increasing nitrite concentration. The results of Experiment II showed that the hatching rate was less affected by ammonia nitrogen, while the survival rate was affected by ammonia nitrogen, the suitable value range was 0–0.6 mg/L. The results of Experiment III showed that the incubation rate was less affected by pH, while the survival rate was affected by pH. The survival rate of the pH 7.7 or pH 8.4 group was significantly higher than that of the other three groups. The results of Experiment IV showed: (1) the LC50 of nitrite for 96 h was 11.43 mg/L, and the safe SC concentration was 1.14 mg/L. (2) The survival and growth rate, antioxidant capacity and immune‐related indexes of juveniles in the 0.023 mg/L nitrite concentration group were the lowest. In summary, to obtain a stable and high production of red claw crayfish by artificial incubation, it was necessary to keep the concentration of nitrite, ammonia nitrogen and pH value in the appropriate range.